Systematic Literature Review: Cooperative Learning Model On Students' Mathematical Representation Abilities At Middle School Level - Sahda Adilah Nur’aini; ST.Budi Waluya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to determine research trends and describe relevant research results regarding cooperative learning models on the mathematical representation abilities of students at the junior high school/MTs level. The method used in this research is literature study or generally known as Systematic Literature Review (SLR) to answer the problem formulation in the research. This research consists of five stages, namely formulation of research questions (Research Question), literature search (Search Process), determination of inclusion criteria (Inclusion Criteria), assessment of literature sources (Quality Assessment), and data analysis (Data Analysis). The study literature search process was carried out by accessing Google Scholar, Publish or Perish, and Garuda. Data was obtained related to keywords and based on the inclusion criteria, namely 22 articles that met the criteria. The research results from reviewing the 22 articles show that the cooperative learning models most widely used to improve representation abilities are cooperative learning models with the STAD and TPS types. The most published articles regarding cooperative learning models on representational abilities were in 2019. The description of research results related to cooperative learning models on representational abilities is that they are able to improve the mathematical representational abilities of students at the SMP/MTs level and equivalent. The cooperative learning model can be combined with appropriate media, strategies and approaches so that it can improve students' mathematical representation abilities.